Inovasi Pembangunan Desa Ramah lingkungan melalui pengelolaan Bank Sampah Bunda di Desa Kalirejo Kecamatan Gondangwetan Kabupaten Pasuruan - Mar'a Saliha Sumantri, Cahya; Satria Hadingra, Mahendra; Fathurrohman, Amang; Kinanti Sutama, Daning (Yayasan Pusat Kemanusiaan dan Transformasi Sosial, 2024)
This study aims to examine the innovation of environmentally friendly village development through the management of the Bank Sampah Bunda in Kalirejo Village, Gondangwetan District, Pasuruan Regency. The program focuses not only on reducing the volume of waste disposed of in landfills but also empowering the community, particularly women, in the efficient and environmentally friendly waste management. The management of the waste bank is expected to raise community awareness about the importance of better waste management, strengthen social structures, and provide economic benefits for the village community. Collaboration between the village government, the community, and other sectors, along with the development of sustainable programs, is key to the success of creating an environmentally friendly village that can improve the quality of life for the people of Kalirejo Village.